2012
DOI: 10.1109/tcsi.2012.2185308
|View full text |Cite
|
Sign up to set email alerts
|

Correction Structures for Linear Weakly Time-Varying Systems

Abstract: This paper presents correction structures compensating for the impact of linear weakly time-varying systems on bandlimited signals. The proposed structures can be used for the postprocessing and preprocessing of linear weakly time-varying systems which complements and generalizes the literature on iterative postcorrection methods. Furthermore, the precorrection of mixed-signal systems is discussed by investigating the computationally efficient preprocessing of nonuniform zero-order-hold signals in digital-to-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The modification was presented for the Richardson iteration and its utilization for post-and pre-linearization was discussed in detail. It was shown that the resulting method is a generalization of the equalizer for linear weakly time-varying systems in [21] and that it may be regarded as a generalization of the post-linearizer in [13] and the P th-order inverse. Due to the iterative structure of the proposed linearizers, their computational cost scales with the required accuracy via the employed number of iterations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The modification was presented for the Richardson iteration and its utilization for post-and pre-linearization was discussed in detail. It was shown that the resulting method is a generalization of the equalizer for linear weakly time-varying systems in [21] and that it may be regarded as a generalization of the post-linearizer in [13] and the P th-order inverse. Due to the iterative structure of the proposed linearizers, their computational cost scales with the required accuracy via the employed number of iterations.…”
Section: Discussionmentioning
confidence: 99%
“…As the corresponding structural modifications equal those for the method in [21], a detailed discussion thereof is omitted here (see also Section VII-A).…”
Section: Conditions For Convergencementioning
confidence: 99%
See 2 more Smart Citations
“…The common factor is that the information found in the output y is used to improve the input, but the algorithm is not necessarily similar to (3.1). One application where iterative solutions are often used is analog-to-digital converter (adc) correction, such as in Soudan and Vogel [2012].…”
Section: Iterative Learning Controlmentioning
confidence: 99%